Comparison of dot enzyme linked-immunosorbent assay (dot-ELISA) kit with other serological tests for the detection of Brucella antibodies in sheep and goats - Agarwal, G S; Singh, S V; Batra, H V (The Indian Journal of Animal Sciences, 2012)
A field based dot enzyme-linked immunosorbent assay (dot-ELISA) kit for detection of Drucetra antibodies in sheep and goats was evaluated in an organized farm where brucellosis was endemic. Goats (1 666) and sheep (666) were tested by the dot-ELISA kit and results compared with SAT and CFT. Among goats, 1 571 animals were negative and 31 were positive to the kit and to the SAT and CFT. Anti-complementary activity was observed in 36 sera samples and 28 animals with mismatch results. In sheep, 91 samples produced positive and 511 gave negative reaction to the kit, SAT and CFT with mismatch observed in 53 animals. For the subsequent testing of 156 sheep and goats sera samples, plate-ELISA was also included along with the SAT and CFT. Under this category, 37 samples were positive and 66 were negative to dot-ELISA kit and to 3 other serological tests. Considering the animals those were either positive or negative to both plate-ELISA and CFT, the kit had a sensitivity of 97.9% and specificity of 89.8%. Similarly, SAT had a sensitivity of 75.5% and specificity 84.7%.